Fiscal space and government debt sustainability: empirical analysis based on Chinese national debt - Zhang, Huiyu; Vveinhardt, Jolita; Xiao, Jianhua; Máté, Domicián (Transformations In Business & Economics, 2026)
Grounded in the intertemporal budget constraint theory , this paper defines ’fiscal space’ as a core indicator of debt sustainability and employs a VECM model to analyze China’s national debt data from 1994 to 2023. The findings reveal that economic growth is the most critical factor for expanding fiscal space, exerting a rapid and sustained positive effect in both the short and long term. The tax burden and population aging have a limited positive impact on fiscal space but may exert long-term pressure on its growth. The effect of inflation on fiscal space is minor and inconsistent. A mismatch between the fiscal revenue and expenditure significantly hinders the expansion of fiscal space. Fostering the high-quality economic growth , enhancing fiscal revenues , and optimizing the management of fiscal revenues and expenditures are crucial for safeguarding China’s government debt sustainability.